Analysis of the Value of Character Education in the Surakarta Style Javanese Bridal Paes and Its Relevance for Javanese Language Learning in Elementary Schools - Rahadini, Astiana Ajeng; Wijayanti, Kenfitria Diah; Veronika, Prima; fitriana, Tya Resta; Sulaksono, Djoko; Lestari, Winda Dwi; Waluyo, Budi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
This research was a qualitative descriptive research using a semiotic approach. This research aims to analyze the value of character education contained in the symbols in the Surakarta style Javanese bridal paes and its relevance as the Javanese language learning material for elementary school level. The symbols in Javanese bridal paes are a medium for transforming noble values containing Javanese cultural teachings for bridal couples in particular and Javanese society in general, especially the younger generation. This is closely related to character development based on local genius. Therefore, this research tries to describe the symbols in Surakarta style Javanese bridal paes as a manifestation of character education values. Each part in Javanese bridal paes is a representation of local wisdom intended to be a medium for educating noble character. The main data collection techniques are direct observation, interviews, documentation of Javanese Surakarta style brides which are strengthened by documentation analysis. For the validity of the data, credibility techniques are used which are carried out by: 1) diligent observation, 2) triangulation of methods and sources, 3) peer discussion, 4) adequacy of references. The data validity technique uses theory triangulation and source triangulation. The data analysis technique in this research uses Charles Sanders Pierce's semiotic analysis technique. The research results show that each part of the Surakarta style Javanese bridal paes is a symbol that contains noble Javanese cultural values which can be a guide for the bridal couple and relevan for Javanese Language Learning in Elementary Schools.